The Influence of Particulated Autogenous Bone on the Early Volume Stability of Maxillary Sinus Grafts with Biphasic Calcium Phosphate: A Randomized Clinical Trial. (28th May 2013) - Kühl, Sebatian; Payer, Michael; Kirmeier, Robert; Wildburger, Angelika; Acham, Stephan; Jakse, Norbert
Abstract Background It is unknown whether autogenous bone impacts the grafts' stability when added to biphasic calcium phosphate (BCP) within the first six months of maxillary sinus augmentation (MSA). Purpose To investigate the volume stability of BCP alone and in mixtures with autogenous bone for MSA. Materials and Methods Bilateral maxillary sinus augmentation was performed in eight patients in a split‐mouth design using BCP at the control site and adding particulated autologous bone at the test site (BCPAB). Based on 16 computed tomography (CT) the volumetric changes were evaluated using the Voxim® software (version 6.3, IVS Technology GmbH, Chemnitz, Germany) by comparing the graft volumes within two weeks of the sinus lift procedure with CT data obtained six months later. Changes of the graft volumes were calculated and statistically significant differences between the two groups were evaluated. Results Overall, the volumes decreased by 15% for BCP and 18% for BCPAB. The time‐dependent decreases were statistically significant in both groups. Differences between the two groups were not statistically significant (p = .065). Conclusions An evident decrease of graft volume over the first 6 months of healing has to be expected irrespective of bone graft composite. Autogenous bone seems to have no evident impact on the volume decrease when added to BCP.